Graced Life After All? Terrorism and Theology on July 22, 2011. Issue 3 (15th September 2015) - Salomonsen, Jone
Abstract: On the afternoon of July 22, 2011, a white Norwegian killed seventy‐seven people in and around Oslo. A majority of those killed where Social Democratic youth, camping on the island of Utøya. Dressed as a Norwegian policeman, Anders Behring Breivik took the ferry over to the island and shot sixty‐nine children with a pistol and a semi‐automatic gun. The weapons were carved with Rune names and dedicated to Thor and Odin, the war gods in Norse mythology. About ninety minutes before the attacks, Breivik had published a 1, 500‐page manifesto on the Internet, urging radical nationalists in Europe to defend Christianity by fighting back Islamic migration, multiculturalism, and feminism. I propose to analyze how a new project linking "Christian and pagan" was launched through the Oslo massacres. I also make a distinction between the sacrificial aspects of a bloody massacre, and the non‐bloody acts of love that manifested among surviving youth at Utøya, and ask if these contrary acts express, or at least involve, two radically different ways of doing religion.